Audiovisualidades Paikianas: uma arqueocartografia por artefatos da tecnocultura audiovisual contemporânea em ambientes on-line - Corso, Aline (Universidade do Vale do Rio dos Sinos, 2023)
With technocultural, imagetic and memorial perspectives, the thesis exercises the interrelation between communication, arts and image technologies in terms of methodologies, concepts and objects, seeking to understand how paikian audiovisualities - understood as an audiovisual quality that is authenticated from the perception of durations (ethical, aesthetic and technical) in Nam June Paik's media artworks are updated in artifacts of contemporary audiovisual technoculture in online environments. Through the creation of an artisanal technomethodological arrangement using the combinations of intuition and archaeocartography, which articulates cartography and media archeology procedures, in addition to the invention of an operational route inspired by the idea of random access, by Nam June Paik, two archaeocartographic tours are carried out. In the first one, it appears that the world(s) of Paik's art is complex and convergent in terms of forms, technologies and aesthetics and can be divided into five major periods: Incubation, Experimentation, Transformation, Expansion and Consolidation. The main technocultural marks found in Nam June Paik are globalism, participation, unpredictability, duality, communication, coexistence, information, randomness, experimentation, playfulness, humor, zen, irony, time, memory, provocation, surveillance, politics, religiosity, flow, multiplicity, multisensoriality, hybridity, virtuality, illusion, manipulability and mutability. In the second round, four constellations were developed, named based on characteristics shared with processes and cultural manifestations in South Korea, the country of birth of the artist: Hanok discusses online environments as “places of memory” in view of the condition of (de)regenerability of Paik, Bibimbap addresses participation, collaboration and remix as expressions of audiovisual technoculture, Newtro examines images that emerge as part of the relationship between the old and the new, bringing clues to think about technostalgic brands, and Ppalli Ppalli produces and evokes senses of acceleration and speed of images in technoculture, especially during the COVID-19 pandemic. The common element that runs through all the constellations is time. In the end, paikian audiovisualities, specifically in online environments, can be defined as an audiovisual quality resulting from the movements triggered by the constellations, understood as dialectical images, which, as a whole, configure a paikian galaxy, always in becoming, to the ways in which the artist put himself in flux. It endure and are (de)regenerated through a mixture of different elements (technical, aesthetic, philosophical, cultural and social, etc.), mainly bringing traces of nostalgia, experimentation and collaboration, provoking us to think, among other things, about the exacerbated exposure of schizophrenic audiovisual information.
Keywords: Tecnocultura; Audiovisualidades paikianas; Imagem; Memória; Nam June Paik; Technoculture; Paikian audiovisualities; Image; Memory; ACCNPQ::Ciências Sociais Aplicadas::Comunicação